Situation Report: Bulgaria, 2 May 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Brezhnev to Sofia this Month Zhivkov Interview with Soviet Television Stoyan Gyurov New Ambassador to Moscow May Day Celebration in Sofia International Meeting of Agrarian Parties in Sofia Miscellaneous